Tożsamość niemiecka w nowym tysiącleciu: leitkultur a islam - Barbara Kobzarska-Bar (Świat Idei i Polityki, 2013)
The issue of the national identity became more popular in Germany in the new millennium. It happened due to pliticians’ actions in this country. There is a strand of the national culture canon present in discussions concerning national identity. In contemporary Germany, this issue and the issue of the integration of the foreign population are connected. The crisis of the idea of multiculturalism concerns german law and influences temporary solutions that regulate community life. The purpose of the article is to attract attention to the discursive character of the german national identity and to show examples of political actions that influence its structuring. The presentation of the issue is precluded by the theoretical analysis introducing readers to the topic of the national identity research on the basis of the selected social studies.